A bio-OCLC structure equating to a movable unit of a lattice cellular core for hybrid in-plane morphing applications. (1st March 2020) - Zheng, Jiliang; Li, Renfu; Zhong, Weihong; Li, Yichao
Abstract: Leaf epidermis cell clusters are similar to a lattice cellular core comprising movable units. Inspired by movability and hardness characteristics of leaf epidermis cell walls, a biomimetic Orthogonal Corrugated Lattice Cellular (bio-OCLC) structure is designed and fabricated to be equivalent to a movable unit of the lattice cellular core. When the in-plane stiffness of a flexible face sheet is decreased to increase its in-plane deformations and lower its in-plane actuation forces, its out-of-plane stiffness is also significantly weakened. However, the loss of the out-of-plane stiffness can be offset by increment in the change of support areas of the bio-OCLC structure for the flexible face sheet. Thus, under the condition that the sum of the decrement and increment of the out-of-plane stiffness is zero, the in-plane deformation of the flexible face sheet increases by 56.52%, and the increase of weight of the composite skin is nearly zero. If the movable units in a lattice cellular core possess the ability of formation changes, the support areas of the core for the flexible face sheet can also be modified by the change of the unit formations. Thus, the lattice cellular core comprising movable units is a promising support structure for a flexible face sheet with hybrid in-plane morphing applications.